Perfluoroalkyl and polyfluoroalkyl substances and measures of human fertility: a systematic review. (20th October 2016) - Bach, Cathrine Carlsen; Vested, Anne; Jørgensen, Kristian Tore; Bonde, Jens Peter Ellekilde; Henriksen, Tine Brink; Toft, Gunnar
Abstract: Perfluoroalkyl and polyfluoroalkyl substances (PFASs) are found widespread in the environment and humans. The relation of PFASs to fertility has now been examined in a relatively large number of epidemiologic studies and a synthesis is in order. The aim of this study was to assess the current human epidemiologic evidence on the association between exposure to PFASs and measures of human fertility, with particular emphasis on perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA). Systematic literature searches were initially conducted in MEDLINE and EMBASE and subsequently in references and citations of included papers. Studies were included if they assessed exposure to PFASs in biological samples in relation to reproductive hormones, semen characteristics, or time to pregnancy (TTP). Study characteristics and results were abstracted to predefined forms, and the studies were assessed for the risk of bias and confounding. Sixteen studies investigated the association between PFAS exposure in men and semen parameters, reproductive hormone levels, or TTP. There was a lack of consistent results among the numerous investigated exposure-outcome combinations. However, subtle associations between higher PFOS and lower testosterone or abnormal semen morphology cannot be excluded. Eleven studies assessed the association between PFAS exposure in women and TTP or reproductive hormones levels. Four of eight studies found prolonged TTP with higher PFOS or PFOA, but only one study found an association when restricting to nulliparous women. In men, there is little evidence of an association between PFAS exposure and semen quality or levels of reproductive hormones. For PFOS and PFOA, the literature indicates an association with female fecundability in parous women, which is most likely not causal.